MENILIK SIKAP BAHASA REMAJA: UPAYA MEMPERTAHANKAN CARA BERBAHASA INDONESIA DALAM RANAH MEDIA SOSIAL - Latifah, Ashpia; Nanda, Nabiilah Chaermy; Nuryani, Nuryani (Jurnal Bahastra, 2023)
The era of globalization which is marked by the development of progress in all things, including technology and information has made social media an effective and unique means of communication for people in cyberspace. Language as a communication tool is an important and inseparable tool in human life, so it is interesting to study further. The use of language in social media is currently a concern of linguists, ignorance of language use on social media is caused by technology itself and the influence of foreign languages on social media. The facts show that Indonesian words can take on new meanings on social media, besides that a lot of vocabulary is found on social media because of the cause and effect of foreign languages, the purity of the Indonesian language is fading. Therefore, this study aims to describe adolescent language attitudes towards Indonesian in the realm of social media and describe the efforts that can be made to maintain the Indonesian way of speaking in the realm of social media. This study used a quantitative approach, sampling was done using google form and the results of the questionnaire were calculated using the Likert scale method. The results of the study indicate that the attitude of adolescents' language towards Indonesian in the realm of social media is in the positive category. However, awareness of adolescent Indonesian norms still needs further attention. The positive attitude of adolescents shown in the results of this study needs to be maintained and the low level of language attitude in the aspect of norm awareness needs to be improved so that Indonesian language in the digital era is maintained.